An environmental cost basis for regulating aviation NOx emissions. (1st May 2022) - Miller, Cassandra J; Prashanth, Prakash; Allroggen, Florian; Grobler, Carla; Sabnis, Jayant S; Speth, Raymond L; Barrett, Steven R H
Abstract: Combustion in aircraft engines results in the formation of nitrogen oxides (NOx ) and carbon dioxide (CO2 ), among other species. NOx impacts air quality and is an indirect contributor to radiative forcing, while CO2 is a long-lived greenhouse gas. The International Civil Aviation Organization sets limits on NOx emissions from commercial aircraft, where for engines with a rated thrust greater than 89 kN the allowable NOx production per unit rated thrust is defined as a function of engine overall pressure ratio (OPR). This definition links the engine thermodynamic cycle, and implicitly fuel burn and CO2 emissions, to allowable NOx levels. These regulations have historically been evaluated and implemented with a focus on reducing adverse air quality impacts around airports, but the thermodynamic efficiency tradeoff with CO2 requires additional analysis to quantify net environmental impacts. This paper introduces a social cost basis for evaluating aviation NOx emissions regulations and quantifies the implied CO2 and NOx attributable air quality damage, climate damage, and fuel costs associated with the emissions standard. We show that higher overall pressure ratio engines operating at the current NOx regulatory limit are allowed more environmental damage per unit rated thrust than lower overall pressure ratio engines, resulting in variable social costs per unit thrust (i.e. fuel and environmental costs combined) across the engine design space. This is a consequence of the definition of the regulation today, where higher pressure ratio engines are allowed higher NOx emissions. Alternative regulation definitions are evaluated which consider the engine cycle and combustor together. Achieving constant social costs requires a regulatory limit where the increase in allowed NOx emissions tapers off at higher pressure ratios, corresponding to the diminishing marginal efficiency improvements due to increasing OPR in that region.